Rape myth adherence among campus law enforcement officers - Smith, Molly (Criminal justice and behavior, 2016)
Campus police agencies are often the first, if not only, responders to sexual assault incidents occurring on college campuses. Little is known, however, regarding the attitudinal dispositions of these officers, specifically their acceptance of rape myths and the effect this has on case processing. The current study addresses this gap in the literature by examining attitudes toward and perceptions of sexual assault among a sample of campus law enforcement officers in Texas. This was done through the administration of a short survey to a sample of campus law enforcement officers prior to their attendance at a sexual assault-focused training, as well as all campus police chiefs via the Internet. Survey items inquired about officers? careers in law enforcement, contact with victims, and perceptions of sexual assault. Results suggest that officers? adherence to rape myths is strongly related to their perceptions of campus sexual assault incidents and their attitudes toward victims. Suggestions for future research and policy are offered.